'Read ten thousand books, walk ten thousand miles': geographical mobility and capital accumulation among Chinese scholars. Issue 2 (15th May 2012) - Leung, Maggi W H
Abstract : International movements of scientists and researchers have become more common in the increasingly inter‐connected global knowledge economy. Geographic mobility is often perceived as a key to academic excellence and career advancement by scholars, especially in advanced economies. In China, where international geographical mobility is a newly‐gained privilege after the advent of the Open Door Policy, academics belong to one of the most mobile subsets of the population. This paper interrogates the impact of academic mobility at the individual level among Chinese scholars who have conducted research visits in Germany. Specifically, the paper operationalises the equivocal notion of personal development with the concepts of capital accumulation and conversion (after Pierre Bourdieu). Drawing upon findings from 64 in‐depth interviews with Chinese scholars of postdoctoral level or above and six key informants, and a postal survey (123 Chinese scholars with mobility biography to Germany), this paper illustrates how geographical mobility can be conceptualised as a form of capital that can be accumulated and converted to cultural, social, economic and symbolic capital. While geographical mobility is predominantly considered as a capital for positive self‐ and professional development, examples also demonstrate the potential detrimental effect on social capital, especially among young Chinese scholars. Using an agent‐centred approach, this paper argues against a mechanical translation of geographical mobility to capital accumulation, but for a grounded understanding of the highly individualised and contextualised development processes.